1991
DOI: 10.1042/bj2790863
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of chylomicron remnants and β-migrating very-low-density lipoproteins by the remnant receptor of parenchymal liver cells is distinct from the liver α2-macroglobulin-recognition site

Abstract: The uptake in vivo of chylomicrons and beta-migrating very-low-density lipoprotein (beta-VLDL) by rat liver, which is primarily carried out by parenchymal cells, is inhibited, 5 min after injection, to respectively 35 and 8% of the control values after preinjection of lactoferrin. The decrease in the uptake of lipoproteins by the liver caused by lactoferrin is a specific inhibition of uptake by parenchymal cells. Competition studies in vitro demonstrate that chylomicron remnants and beta-VLDL compete for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 58 publications
6
53
0
Order By: Relevance
“…It is generally accepted, however, that for the initial liver recognition of remnants, the so-called "capture step," additional systems are needed. The initial sequestration step was suggested to involve heparan sulfate proteoglycans (5,12), the lipolysis-stimulated receptor (13)(14)(15), a TG-rich lipoprotein receptor (16,17), the asialoglycoprotein receptor (18), LPL (19), and/or hepatic lipase (20), while we also provided evidence for a specific remnant receptor (21)(22)(23) to function as an initial recognition site for remnants. However, the removal pathways of chylomicrons and their remnants remain complex, and the precise mechanism of recognition is still unclear and under debate (1-3).…”
mentioning
confidence: 82%
“…It is generally accepted, however, that for the initial liver recognition of remnants, the so-called "capture step," additional systems are needed. The initial sequestration step was suggested to involve heparan sulfate proteoglycans (5,12), the lipolysis-stimulated receptor (13)(14)(15), a TG-rich lipoprotein receptor (16,17), the asialoglycoprotein receptor (18), LPL (19), and/or hepatic lipase (20), while we also provided evidence for a specific remnant receptor (21)(22)(23) to function as an initial recognition site for remnants. However, the removal pathways of chylomicrons and their remnants remain complex, and the precise mechanism of recognition is still unclear and under debate (1-3).…”
mentioning
confidence: 82%
“…One possibility is that uptake of GV-LDL occurs through a multistep process beginning with an initial binding to cell-surface heparan sulfate proteoglycans (HSPG), followed by their uptake into cells by a receptor-mediated process that utilizes members of the low density lipoprotein receptor family (34 -36). Several studies have shown that LRP binds apoE-enriched particles (50,51) and that the clearance of apoE-containing particles, such as chylomicron remnants and ␤-very low density lipoprotein, is inhibited by lactoferrin (38,52,53), a molecule that also binds to LRP (37). We tested the possible involvement of LRP in proteoglycan-mediated uptake of GV-LDL using lactoferrin.…”
Section: Discussionmentioning
confidence: 99%
“…One is that proteoglycan binding of GV-LDL may be followed by uptake via a receptor-mediated process that utilizes the LDL receptorrelated protein (LRP), as has been shown for apoE-enriched chylomicron remnants (34 -36). To investigate this possibility, macrophages were incubated with GV-LDL in the presence of lactoferrin (5 mg/ml), which binds to LRP (37) and inhibits uptake of ␤-very low density lipoprotein and chylomicron remnants (38,39). Our results show that addition of lactoferrin has no effect on CE accumulation by macrophages (Fig.…”
Section: Gv-ldl Uptake By Macrophages Ismentioning
confidence: 99%
“…It is believed that the clustering of cysteine-rich type A binding repeats, resembling those found in LDL receptor, is the molecular principle for the ability to bind a variety of ligands so far thought to be unrelated. The physiological importance of recognition of the hitherto identified or proposed ligands -activated c~2-macroglobulin (~2M*), apolipoprotein E (apoE), lipoprotein lipase (LPL), plasminogen activators and complexes with their inhibitor (PA and PA/PAI-1), lipoprotein(a), pseudomonas exotoxin A, human rhinovirus, Lf and the so-called receptor associated protein (RAP) -by a single receptor entity is one crucial question to be answered [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Within the description of miscellaneous ligands of LRP/~2MR also in vitro binding of Lf was demonstrated [1].…”
Section: **Present Addressmentioning
confidence: 99%